2005
DOI: 10.1097/01.tp.0000161250.83392.73
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Hepatitis B and C in Renal Allograft Recipients

Abstract: In the long term, B+ patients had a higher risk of death related to liver disease than C+ patients, and co-infection did not worsen patient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 15 publications
3
59
1
2
Order By: Relevance
“…[2][3][4] Recently, several clinical trials provided with long follow-up, large size, and appropriate statistical approach have demonstrated the negative impact of HCV on patients (Table 1) and graft survival (Table 2) after RT. [5][6][7][8][9][10][11][12][13][14] A recent meta-analysis of clinical and observational surveys found that RT recipients with anti-HCV antibody have an increased risk of mortality and graft failure compared with anti-HCV antibody negative patients.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Recently, several clinical trials provided with long follow-up, large size, and appropriate statistical approach have demonstrated the negative impact of HCV on patients (Table 1) and graft survival (Table 2) after RT. [5][6][7][8][9][10][11][12][13][14] A recent meta-analysis of clinical and observational surveys found that RT recipients with anti-HCV antibody have an increased risk of mortality and graft failure compared with anti-HCV antibody negative patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed that 5 years patient survival rate was worse in HbsAg(+) patients, while another study revealed that HbsAg positivity had no impact on patient survival rate (12)(13)(14)(15)(16). However, a study have revealed that 5 years patient and graft survival rates were similar between HbsAg(+) and HbsAg(-) patients (1).…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have been performed in order to determine the effects of HBV infection on graft or survival rates and liver complications after Rtx to HBV(+) patients (1,(9)(10)(11)(12)(13)(14)(15)(16)(17). Also, the effectivness of antiviral treatment, interferon or nucleoside analogues in HBV(+) patients have been demonstrated by some authors (16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] However, after long-term follow-up study results (> 10 y) were published, data about the negative effect of HCV infection on patient and graft survival began to accumulate. [18][19][20] The reported relative risk of mortality in patients with HCV was 1.59 to 1.93, and relative risk of graft loss was 1.5. Liver-related mortality accounted for at least some of the excess mortality, and most deaths were from sepsis and cardiovascular causes.…”
Section: Discussionmentioning
confidence: 99%